Application of PMF receptor model merging with PAHs signatures for source apportionment of black carbon in the continental shelf surface sediments of the Bohai and Yellow Seas, China. Issue 2 (15th February 2016) - Fang, Yin; Chen, Yingjun; Tian, Chongguo; Lin, Tian; Hu, Limin; Li, Jun; Zhang, Gan
Abstract: Black carbon (BC) and polycyclic aromatic hydrocarbons (PAHs) are byproducts generated from the incomplete combustion of organic materials, including fossil fuels and biomass. The similar production processes shared by BC and PAHs provide the possibility to infer the BC sources using the PAHs signatures. This study successfully utilized data sets of BC and PAHs analyzed from the continental shelf surface sediments of the Bohai and Yellow Seas to a standard receptor model of positive matrix factorization (PMF) to apportion the sources of BC in the sediment matrix. Results showed that combustion of fossil fuels (i.e., coal and oil/petroleum) accounted for an average level of 83 ± 5% of the total BC preserved, which was significantly higher than that from the biomass burning (17 ± 5%). The spatial distributions of the fossil BC concentrations and percentages differed significantly from those of the biomass BC, implying their different geochemical behaviors in the continental shelf regimes and further emphasizing the importance to effectively differentiate between fossil BC and biomass BC. In addition to the relative proportions of the BC subtypes (char‐BC/soot‐BC), the regional‐specific hydrodynamic conditions, including the cold cyclonic eddy, resuspension and coastal current, also exerted a significant influence on these spatial variations. Key Points: The sources of sediment BC were apportioned by PMF receptor model merging with PAHs signatures Fossil fuels combustion was the dominant source of BC preserved in the BS and YS surface sediments BC subtypes and hydrodynamic conditions affected the spatial variations of fossil BC and biomass BC